PENGARUH KUALITAS PELAYANAN, KEPERCAYAAN DAN FASILITAS KAMPUS TERHADAP KEPUASAN DAN DAMPAKNYA KEPADA LOYALITAS MAHASISWA POLITEKNIK INDONESIA VENEZUELA - Geta Ambartiasari; Abdul Rahman Lubis; Syafruddin Chan (Jurnal Manajemen Inovasi, 2017)
ABSTRACTThis study aimed to analyze the influence of the service quality, student’s trust and campus facilities to the satisfaction of students and its impact on student loyalty at polytechnic Indonesia Venezuela. The samples were 230 respondents active status as a student in Indonesia Polytechnic campus Venezuela. Collecting data using questionnaires and then the data were analyzed with AMOS software using statistical tools Structural Equition Modelling (SEM). The study found that the services quality, student’s trust and campus facilities effect on student satisfaction. The direct effect of these three variables on the satisfaction of students rated significantly. Service quality, and campus facilities affect the loyalty of students, while the students trust has no influence on student loyalty at Polytechnic Indonesia Venezuela. Student satisfaction effect on student loyalty. The direct effect of student satisfaction to student loyalty rated significantly. It can be concluded that student satisfaction can act as an intervening variable between the loyalty of students on the one side with the services quality, student trust and campus facilities on the other side. Keywords : Service Quality, Trust, Facilities, Student Satisfaction, Student Loyalty